A cross-sectional study of prevalence of overweight and hypertension among veterans in Eastern Uttar Pradesh - Adhya, Saibal; Tyagi, Arun; Anand, Vivek; V., Pavithra (International Journal Of Community Medicine And Public Health, 2021)
Background: Health problems of veterans have not been studied extensively. Obesity though not a major problem while in service, could be a major factor leading to morbidity and mortality due to lifestyle diseases seen among overweight/obese people. Methods: Status of overweight and hypertension was studied among ex-servicemen population of a military station in the age group of primarily 50-70 years. Results: More than 35% veterans were found to be overweight/obese. Underweight was a more serious problem than overweight among those above 70 years of age. Prevalence of hypertension was also high (25%). There was weak association of overweight with hypertension among ex-servicemen because the problem seems to appear late in life. This association was stronger upto 60 years of age after which it starts decreasing. Conclusions: The problems of overweight and obesity and hypertension constitute considerable health burden among the veterans. However, a significant causal association could not be established between overweight and hypertension.